Analisis Kesalahan dalam Memecahkan Masalah Kombinatorika Ditinjau dari Gaya Kognitif - Yunis Sulistyorini; Dian Fitri Argarini; Nok Izatul Yazidah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Error analysis is integral part of mathematics learning. This qualitative research aims to describe the types and causes of student errors in solving combinatorics problem based on cognitive style. Subjects are high school students with field independent (FI) and field dependent (FD) cognitive style. Error analysis refers to Newman's error analysis. FI and FD students have same errors that are comprehension error at stage of understanding problem; processing skills error and encoding error at the stage of carrying out the plan. The causes of the errors are viewed from the cognitive factors, namely understanding students' concepts in solving problems. FI students have a deeper understanding and make careless error while the FD students have a lack of understanding of the concept which cause more error. The cause of errors in both students is also due to the accumulation of errors at stage of understanding problem.